GEORGIA’S GEOPOLITICAL LANDMARKS: IS THERE A SHIFT? - GACHECHILADZE, Revaz (CENTRAL ASIA AND THE CAUCASUS, 2005)
On 30 October 2004, we all learned that the NATO Council endorsed the Individual Partnership Action Plan between NATO and Georgia. The diplomatic communities of many countries assessed this as a serious step toward Georgia’s integration into NATO. No specific dates were cited; the NATO Secretary General who visited Tbilisi several days after the announcement cautioned our leaders that they had to cope single-handedly with the gravest of our problems—separatism. The public, however, is inclined to believe Mikhail Saakashvili, who says that Georgia will join NATO during his presidential term. The country has already started readjusting its armed forces to the NATO standards. Under the agreements with the United States, by the end of 2004 there were 850 Georgian servicemen stationed in Iraq as part of the coalition forces (this is a large figure for a country with an army of 14,000-15,000). In so doing, Georgia is demonstrating its intention to shift its foreign policy vector westward; for over two centuries, until the end of the 20th century, the country (wittingly or unwittingly) was north oriented. It should be said, however, that starting in the mid-1990s, the country’s leaders have been insisting on a multi-vectoral foreign policy, which means that the country has abandoned its orientation only toward Moscow. Diplomatic efforts in this direction never slackened, yet (for objective and subjective reasons) the country’s real integration into Europe (by this I mean integration into NATO and the EU) looked like a distant and pretty unrealistic goal. The country had to concentrate on its own survival; it needed (and still needs) energy fuels and had to depend (and still has to depend) on Russia for them. The new Georgian leaders brought to power by the “Rose Revolution” of November 2003 are obviously pro-Western. All political forces, including the large opposition parties, agree with this, or do not oppose this course. The coming geopolitical shift in the key South Caucasian state poses the question: Why is a small country (Georgia in our case) forced to seek strategic partners far from its borders? Is its NATO partnership real? In other words: Will it be welcome in the West? To correctly identify a country’s geopolitical goals and hence its future, its past must be analyzed and put into the broad geographical context. This alone will make it possible to discover the geopolitical code on which the country’s foreign policy rests; to be more exact, the geopolitical code determines the country’s interests, as well as identifies the threats to these interests and the nature of possible responses to these threats. with a small country, the geopolitical code normally remains at the local level and suggests strategic assessments of its neighbors when shaping its foreign policy. Only the world superpowers operate with geopolitical codes at the global level. A small country, however, cannot remain indifferent to the global geopolitical situation and, especially, to the superpowers’ interests and designs. While trying to adjust itself to global geopolitics, a small country can find its niche on the world arena to remain safe or to survive.